2017
DOI: 10.1515/jwld-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial neural network (ANN) for prediction of sediment loads, application to the Mellah catchment, northeast Algeria

Abstract: In this study, we present the performances of the best training algorithm in Multilayer Perceptron (MLP) neural networks for prediction of suspended sediment discharges in Mellah catchment. Time series data of daily suspended sediment discharge and water discharge from the gauging station of Bouchegouf were used for training and testing the networks. A number of statistical parameters, i.e. root mean square error (RMSE), mean absolute error (MAE), coefficient of efficiency (CE) and coefficient of determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The multi-layer perceptron consists of an output layer, hidden layers and input layers. Depending on the type of the dataset, topology and statistical errors in the ANN, the count of the hidden layers may be one or more [88]. Each layer in the network involves a precise number of neurons associated with connection weights and activation functions.…”
Section: Annmentioning
confidence: 99%
“…The multi-layer perceptron consists of an output layer, hidden layers and input layers. Depending on the type of the dataset, topology and statistical errors in the ANN, the count of the hidden layers may be one or more [88]. Each layer in the network involves a precise number of neurons associated with connection weights and activation functions.…”
Section: Annmentioning
confidence: 99%
“…It is also applicable in all the situations where there is a nonlinear relation between a predictive variable and a predicted variable. (Bouzeria et al, 2017). The ANNs are generally made up three layers as input, hidden and output which are linked to artificial neurons.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…An extensive review of ANN applications in the hydrological field for the estimation and prediction of numerous hydrological parameters has been acknowledged by the ASCE Task Committee [30,31]. In the last two decades, studies have shown that artificial neural networks (ANNs) have promising results in terms of modelling and forecasting streamflow [32,33], reservoir water level [34,35], and suspended sediment in rivers [2,[36][37][38]. The ANN model is especially employed where basic physical interactions are not entirely known, but there are sufficient data to train a network.…”
Section: Introductionmentioning
confidence: 99%